2022
DOI: 10.3390/vaccines10050792
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward COVID-19 Vaccines among Patients with Complex Non-Communicable Disease and Their Caregivers in Rural Malawi

Abstract: Current low COVID-19 vaccination rates in low- and middle-income countries reflect an inequitable global vaccine distribution; however, local attitudes towards the COVID-19 vaccine are an important factor to meet vaccination benchmarks. We describe attitudes toward the uptake of the COVID-19 vaccine and perceptions among patients with NCDs and their caregivers using cross-sectional data collected through telephone interviews in Neno, Malawi. Out of 126 survey respondents, 71% were patients, and 29% were caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In addition, vaccination status was a significant predictor of fear of vaccination in the regression analysis. These results are consistent with previous studies, showing that fear of vaccination-related harm and side effects is the crucial reason to refuse vaccination [ 4 , 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Alzubaidi et al [ 59 ] recommended reducing fears about the adverse effects of vaccination as a prevention or intervention strategy to increase COVID-19 vaccination uptake.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, vaccination status was a significant predictor of fear of vaccination in the regression analysis. These results are consistent with previous studies, showing that fear of vaccination-related harm and side effects is the crucial reason to refuse vaccination [ 4 , 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Alzubaidi et al [ 59 ] recommended reducing fears about the adverse effects of vaccination as a prevention or intervention strategy to increase COVID-19 vaccination uptake.…”
Section: Discussionsupporting
confidence: 93%
“…For example, on 9 June 2021 (when the data were collected in the current study), there were 24–25% of fully vaccinated people in Germany, Poland, and Slovenia, whereas 56% in Israel [ 12 ]. The main barrier to vaccination is distrust in the effectiveness of vaccination and fear of vaccination side effects, including infertility, harm, severe disability, or even death [ 4 , 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Aron et al [ 22 ] describe attitudes toward the uptake of the COVID-19 vaccine and perceptions in patients with non-communicable diseases (NCDs) and their caregivers in rural Malawi. Vaccine uptake and intention to vaccinate among this group of vulnerable non-communicable disease patients and their caregivers in rural Malawi were three times higher than the general public’s current vaccination rate but substantially below the vaccination target of 70%.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also found high stigma associated with COVID-19 and vaccinations. 7 , 8 Lastly, the other highlighted limitations including of use of a fixed ratio of FEV1:FVC to define COPD, low smoking prevalence and inability to distinguishing between COPD phenotypes due to not being able to report TLC and RV, although it is believed that there would be more biomass phenotypes with high biomass exposure are acknowledged in our paper. We look forward to additional opportunities to illuminate further data on COPD with more specific diagnostics and larger cohorts.…”
Section: Dear Editormentioning
confidence: 95%